Seismic vulnerability assessment of ancient masonry building: an experimental method - Mendes, N. (2010)
This paper presents a review of the methods for seismic vulnerability assessment, together with an experimental method based on shaking table testing. This method is applied to a Portuguese masonry building typology with stone walls and timber floors, subjected to increasing earthquake damage. Traditional-like materials and techniques are used in the building. The vulnerability curves are presented and the damage indicator is correlated with the crack patterns and EMS 98.